Zirconia as a Dental Biomaterial - Della Bona, Alvaro (Materials (Basel), 2015)
Ceramics are very important in the science of dental biomaterials. Among all dental ceramics, zirconia is in evidence as a dental biomaterial and it is the material of choice in contemporary restorative dentistry. Zirconia has been applied as structural material for dental bridges, crowns, inserts, and implants, mostly because of its biocompatibility, high fracture toughness, and radiopacity. However, the clinical success of restorative dentistry has to consider the adhesion to different substrates, which has offered a great challenge to dental zirconia research and development. This study characterizes zirconia as a dental biomaterial, presenting the current consensus and challenges to its dental applications.